MicroRNA-1 and Circulating Microvesicles Mediate the Protective Effects of Dantonic in Acute Myocardial Infarction Rat Models - Sun, Tingting; Zhang, Lihua; Li, Xinxin; Chen, Fengfei; Li, Yanchuan; Ma, Xiaohui; Yu, Feng (Frontiers in Physiology, 2018)
Abstract: Aim: To investigate the protective effect of dantonic in ischemic myocardial damage by evaluating the expression of circulating microvesicles (MVs) and microRNA-1 (MIR-1) in two animal models Methods: Two animal models of myocardial ischemia were established that wereisoproterenol-induced myocardial ischemia (ISO-AMI) rat model and the acute myocardial infarction rat model induced by ligation of the left anterior descending coronary artery (LAD-AMI) of rat. To investigate the protective effect of dantonic, we observed the myocardial infarction size, CK, LDH, AST activities, cardiac troponin I (cTnI) level in serum, and the plasma levels of miR-1 and MVs. Results: The results showed that pretreatment with dantonic significantly attenuated the LAD-AMI induced myocardial damage by decreasing the size of myocardial infarction, CK, LDH, AST activities and cardiac troponin I (cTnI) level in serum. High dose dantonic treatment could significantly abrogate the increased plasma levels of miR-1 and MVs as compared to the LAD rat model. In addition, pretreatment with dantonic also showed a significant myocardial protective effect through reducing the expression levels of CK, LDH and AST as compared to the ISO-AMI model. Whereas the cTnI level was no significant difference between model group and control group，suggesting that the model caused less myocardial damage. In the ISO-induced myocardial ischemia model, there is no significant difference between the model group with the control group of Mvs and Mir-1 levels. This may be that Mir-1 is reported as a biomarker of acute myocardial infarction. The pathological changes of IOS-induced acute myocardial ischemia model are also different from those of acute myocardial infarction. Conclusion: Dantonic showed the protective effect in these two ischemic myocardial injury rat models, whereas the circulating miR-1 and MVs levels were only ameliorated in the LAD rat model.